The Opposition of Kelompok Islam 212 (212 Islamic Group) to Joko Widodo's Government : Strengthening or Weakening Democracy? - Muharam, Moch Mubarok; Widodo , Bambang Sigit; Kasanusi , Kasanusi; Adi, Agus Satmoko; Firmansyah, Faiz Armathori (Journal of Civics and Moral Studies, 2024)
TThis study aims to analyze the opposition of the 212 Islamic Group to the government led by Joko Widodo. This study uses a qualitative approach by conducting in-depth interviews with nine informants from the 212 Islamic Group and the Moderate Islamic Group. In addition to conducting interviews, data was collected from written information from books, online media, and journals. This study concluded that the opposition carried out by ‘Kelompok Islam 212’  (‘the 212 Islamic Group') against Joko Widodo has been carried out for a long time since the President of the Republic of Indonesia became Governor of DKI Jakarta. In that case, on the one hand, the opposition carried out by the group can strengthen democracy because there is a practice of checks and balances on power. Nevertheless, on the other hand, if this group wins, there is concern that the principle of democracy cannot be adequately implemented, because the group carries out exclusive practices politically and religiously.